Dielectric properties of PZT-PCN ceramics under compressive stress - Muangjai Unruan (2018)
In this study, ceramics in PZT-PCN systems with a formula (1-x)Pb(Zr 1/2 Ti1/2) O3-(x)Pb(Co1/3Nb 2/3)O3 (x=0.1-0.5) were prepared by a solid-state mixed-oxide technique. The phase formation and microstructure were studied using x-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. Effects of compressive stress on the dielectric properties of PZT-PCN ceramics were investigated at stress up to 230 MPa using a compressometer. The results clearly showed that the dielectric constant of the PZT-PCN ceramics increased significantly with increasing applied stress, while the dielectric loss tangent showed an opposing trend. The experimental observations have been attributed to a combination of the domain switching and the deaging mechanisms from the application of the compressive stress. © 2008 The Royal Swedish Academy of Sciences.